Warehouse area transformation as a driver of compact city development: The case of Warsaw - Kuzak, Łukasz; Izdebski, Maciej; Maciejewska, Alina (Quaestiones Geographicae, 2025)
One of the most significant challenges in the development of modern cities is the rational development of their space. Effective management of empty areas and other land reserves occurring in the urban fabric and their appropriate development is becoming necessary. This study presents the results of research on the identification of warehouse and industrial areas, as well as auxiliary and post-industrial regions, which have the potential to be successfully transformed towards other functions, specifically housing development. The analysis of available literature and a review of successful implementations of this type of transformation reveal that the key to success is the accessibility of transport and the availability of city services in the transformed area. In addition to accessibility, a vital factor is the size of the transformed area, allowing for the introduction of appropriate development. Thus, a suitability index was developed and calculated based on both factors for Warsaw. Subsequently, the areas with the most significant transformation potential were selected in individual city zones (functional inner city, consolidated urban and suburban). The analysis of the results and a review of the areas with the highest index value indicate the accuracy of the adopted analysis method, potentially selecting areas for transformation in other cities with high investment pressure. Thus, using the proposed methodology, the appropriate use of storage areas may limit urban sprawl and implement the idea of a compact city, which is a response to the ongoing urban crisis.